GAMBARAN PERILAKU IBU DALAM POLA ASUH BALITA DENGAN GANGGUAN SPEECH DELAY (STUDI KASUS DI YPAC KOTA SEMARANG) - Maher, Gicelle Technia; Husodo, Besar Tirto; Kusumawati, Aditya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Speech delay is a developmental disorders that often occurs to toddlers and the numbers are increasing, especially in big cities like Semarang. Speech delay in toddlers (golden age) can cause adverse effects on health and non-health aspects, such as developmental delays, children's social life, and learning difficulties. This encourages parents in Semarang to entrust YPAC as a speech therapy place for their children. For speech delay children, speech stimulation must be done continuously between the therapist and mother at home. However, there were cases of mothers who don’t give speech stimulation routinely. The data on this qualitative descriptive research was collected with in-depth interviews from five research subjects with purposive sampling method. The validity test was done by five triangulation subjects who are close relatives of research subjects, while the reliability test was done by data auditing. Because the subjects show lack of understanding about stimulation, they enroll their children to YPAC speech therapy. However, mother's working hour affects their quality time at home, making them hand over responsibility for stimulation to the therapist. The unique thing that was found in this study was that mother's feelings were affected due to lack of support from their husband, the lack of motivation from the therapist, and no direction for stimulation at home from the therapist. Which makes them feels less confident doing stimulation at home due to fear of making mistakes. These reasons eventually form mother's parenting style that’s too permissive or authoritarian and affects children’s character in the future.